The Role of Skeletal Muscle in Amyotrophic Lateral Sclerosis - Loeffler, Jean‐Philippe (Brain Pathol, 2016)
Amyotrophic lateral sclerosis (ALS) is a fatal adult‐onset disease primarily characterized by upper and lower motor neuron degeneration, muscle wasting and paralysis. It is increasingly accepted that the pathological process leading to ALS is the result of multiple disease mechanisms that operate within motor neurons and other cell types both inside and outside the central nervous system. The implication of skeletal muscle has been the subject of a number of studies conducted on patients and related animal models. In this review, we describe the features of ALS muscle pathology and discuss on the contribution of muscle to the pathological process. We also give an overview of the therapeutic strategies proposed to alleviate muscle pathology or to deliver curative agents to motor neurons. ALS muscle mainly suffers from oxidative stress, mitochondrial dysfunction and bioenergetic disturbances. However, the way by which the disease affects different types of myofibers depends on their contractile and metabolic features. Although the implication of muscle in nourishing the degenerative process is still debated, there is compelling evidence suggesting that it may play a critical role. Detailed understanding of the muscle pathology in ALS could, therefore, lead to the identification of new therapeutic targets.